AzTEC survey of the central molecular zone: data reduction, analysis, and preliminary results. Issue 2 (28th April 2021) - Tang, Yuping; Wang, Q Daniel; Wilson, Grant W; Heyer, Mark H; Gutermuth, Robert A; Schloerb, Peter; Yun, Min S; Bally, John; Loinard, Laurent; Silich, Sergiy; Chávez, Miguel; Haggard, Daryl; et al.
ABSTRACT: We present a large-scale survey of the central molecular zone (CMZ) of our Galaxy, as well as a monitoring program of Sgr A*, with the AzTEC/ Large Millimeter Telescope in the 1.1 mm continuum. Our 1.1 mm map covers the main body of the CMZ over a field of 1.6 × 1.1 deg 2 with an angular resolution of 10.5 arcsec and a depth of 15 mJy beam −1 . To account for the intensity loss due to the background removal process, we combine this map with lower resolution CSO/Bolocam and Planck /HFI data to produce an effective full intensity 1.1 mm continuum map. With this map and existing Herschel surveys, we have carried out a comprehensive analysis of the spectral energy distribution of dust in the CMZ. A key component of this analysis is the implementation of a model-based deconvolution approach, incorporating the Point Spread Functions (PSFs) of the different instruments, and hence recovering a significant amount of spatial information on angular scales larger than 10.5 arcsec. The monitoring of Sgr A* was carried out as part of a worldwide, multiwavelength campaign when the so-called G2 object was undergoing the pericentre passage around the massive black hole. Our preliminary results include (1) high-resolution maps of column density, temperature and dust spectral index across the CMZ; (2) a 1.1 mm light curve of Sgr A* showing an outburst of 140 per cent maximum amplitude on 2014 May 9th May, 2014 but otherwise only stochastic variations of 10 per cent and no systematic long-term change, consistent with other observations.